Does Rectum and Bladder Dose Vary during the Course of Image-guided Radiotherapy in the Postprostatectomy Setting?. Issue 5 (September 2014) - Akin, Mustafa; Oksuz, Didem Colpan; Iktueren, Basak; Ambarcioglu, Pinar; Karacam, Songul; Koca, Sedat; Dincbas, Fazilet Oner
Aims and Background: To assess the variations in actual doses delivered to the rectum and bladder in the course of postprostatectomy radiotherapy using kilovoltagecone-beam computed tomography datasets acquired during image-guided radiotherapy. Methods and Study Design: Twenty consecutive patients treated with intensity-modulated or intensity-modulated arc therapy to the prostate bed were retrospectively evaluated. Both the planning tomography and kilovoltage-cone-beam computed tomography were acquired with an empty rectum and a half-full bladder. Target localization was performed on the basis of soft tissue matching using cone-beam computed tomography scans before each treatment fraction. A total of 16 cone-beam computed tomography scans per patient (acquired at the first 5 fractions and twice weekly thereafter) were used for the assessments. The bladder and rectum were recontoured offline on each cone-beam computed tomography scan by a single physician, and the delivered doses were recalculated. The variations in certain dose-volume parameters for the rectum and bladder (BD2cc, RD 2cc, V40%, V50%, V60%, V65%) were analyzed using the paired t test. Results: Most of the dose volume variations for rectum and bladder were significantly higher than predicted (P <0.05) for the 320 kilovoltage-cone-beam computed tomography sets, except for the doses received by 2 cc of the bladder and V50 and V60 of the rectum. The dose-volume parameters of the bladder did not meet our criteria of V65 ≤25% and V40 ≤50% in 10% and 20% of the patients, respectively. None of the dose-volume histograms showed rectal V65 ≥17%; however, the rectal V40 ≤35% dose constraint was not met in 11 patients. For all patients, the ANOVA test revealed no significant difference between the variations. Conclusion: Actual doses delivered during treatment were found to be higher than predicted, but the majority of calculated bladder and rectal doses remained in the limits of our plan acceptance criteria. Interfraction variability of the rectum and bladder is a major concern in the postprostatectomy radiotherapy setting, even when patients are instructed about rectal and bladder preparation before the radiotherapy course. Image guidance with cone-beam computed tomography at each treatment fraction may offer a viable tool to account for interfraction variations of the rectum and bladder throughout the treatment course.